Women and Diabetes - Marcia Brown; Linda Bobroff; LaToya J. O'Neal (EDIS)
This document is about the importance of diabetes awareness and care among women. It highlights that women, often primary caregivers, may neglect their own health, leading to undiagnosed diabetes and severe complications. The document emphasizes that diabetes affects women differently than men, with higher risks of heart disease, blindness, and depression. It also notes that women from certain racial and ethnic groups are more at risk. The Take Time to Care campaign by the FDA aims to educate women on diabetes risk factors and encourage testing. Additionally, it provides resources from the CDC, American Diabetes Association, and other organizations for further information and support. Original publication date February 2008.